Makna Kerja Menurut Karl Marx: (Sebuah Kajian dari Perspektif Filsafat Manusia) - Johanis Hence Raharusun (Media (Jurnal Filsafat dan Teologi), 2021)
The essay deals with the essential meaning of work according to Karl Marx. The purpose of the essay is to offer a new perspective on the meaning of work based on the thinking of Marx. Based on the literature review, it presents Marx's concept of work that becomes his critique to the objective conditions of workers who experienced degradation in their work. In Marx’s opinion, the workers were alienated from themselves, from their work milieu and social environment because of the capitalist system that only seeks profit for the owner’s capital. Marx emphasized that work is an existential human act because it contains rational, universal, and autonomous values. Work is also a differentiating activity between humans and animals. It becomes a human means of changing nature, it should be regarded as a process of human self-realization and as a means of socializing with others